sodC-Based Real-Time PCR for Detection of Neisseria meningitidis - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2011)
Real-time PCR (rt-PCR) is a widely used molecular method for detection of Neisseria meningitidis (Nm). Several rt-PCR assays for Nm target the capsule transport gene, ctrA. However, over 16% of meningococcal carriage isolates lack ctrA, rendering this target gene ineffective at identification of this sub-population of meningococcal isolates. The Cu-Zn superoxide dismutase gene, sodC, is found in Nm but not in other Neisseria species. To better identify Nm, regardless of capsule genotype or expression status, a sodC-based TaqMan rt-PCR assay was developed and validated. Standard curves revealed an average lower limit of detection of 73 genomes per reaction at cycle threshold (C-t) value of 35, with 100% average reaction efficiency and an average R-2 of 0.9925. 99.7% (624/626) of Nm isolates tested were sodC-positive, with a range of average C-t values from 13.0 to 29.5. The mean sodC C-t value of these Nm isolates was 17.6 +/- 2.2 (+/- SD). Of the 626 Nm tested, 178 were nongroupable (NG) ctrA-negative Nm isolates, and 98.9% (176/178) of these were detected by sodC rt-PCR. The assay was 100% specific, with all 244 non-Nm isolates testing negative. Of 157 clinical specimens tested, sodC detected 25/157 Nm or 4 additional specimens compared to ctrA and 24 more than culture. Among 582 carriage specimens, sodC detected Nm in 1 more than ctrA and in 4 more than culture. This sodC rt-PCR assay is a highly sensitive and specific method for detection of Nm, especially in carriage studies where many meningococcal isolates lack capsule genes.
Keywords: SUPEROXIDE-DISMUTASE; STREPTOCOCCUS-PNEUMONIAE; CEREBROSPINAL-FLUID; HAEMOPHILUS-INFLUENZAE; BACTERIAL-MENINGITIS; IDENTIFICATION; SEQUENCE; DIAGNOSIS; GENES; RESISTANCE